Biostratigraphy of Lower Sarmord Formation in Kirkuk well no-109. Nouthern Iraq. - Al-Dujile, Luay (Iraqi Journal of Science, 2023)
The study includes biostratigraphy of the Lower Sarmord Formation in well Kirkuk-No-109. North of Iraq, two biozones had been distinguished as follow:1- Choffatella decipiens SCHLUMBRGER Zone.2- Orbitolina discoidea GARS Zone.The age of Formation in this study is determanid as Lower Cretaceous (Hauterivian-early Aptian).Keyword: Lower Sarmord, Formation well Kirkuk-109, Choffatella decipiens and Orbitolina discoidea, Lower Cretaceous